The relationships of manufacturing practices, knowledge transfer, organizational capabilities, towards manufacturing capabilities : Moderating effect of training across industries in Northern region of Malaysia - Mohammad Harith, Amlus (2014)
Malaysia is one of the countries which focus on the manufacturing sector to get income. That is why manufacturing capabilities are an important factor in running and developing a business. Therefore, this study aimed to identify the relationship between the factors that ensure that the manufacturing companies in Malaysia can survive among similar companies in the industry. The factors identified in this study are manufacturing practices, knowledge transfer, organization capability and manufacturing capabilities. Training is a moderating variable in this study. Through a mail survey, a total of 119 companies representing a variety of industries provided feedback. The hypothesis was tested using correlations and regression techniques. These findings support the hypothesis. The multiple regression analysis showed that there were significant correlations between the factors in each of the criteria for manufacturing capabilities. The hierarchical multiple regression analysis was conducted to test the role of the moderating variable in the relationship between the independent variables and the dependent variable. The hierarchical multiple regression results showed that training moderated and enhanced the companies to compete with others. To examine the relationship between manufacturing capabilities, manufacturing practices, knowledge transfer in manufacturing, organization capabilities and training, this research used a technology adoption theory - the Resource- based Theory. The research framework consisted of the following: four manufacturing practices, three knowledge transfer in manufacturing, two organization capabilities, three training as a moderating variables, and four manufacturing capabilities. This research used an adopted survey with a 5-3 point- Likert-scale. To analyze data, SPSS version 19.0 was used to examine the path of relationships between the variables. This study will be beneficial to the shareholders and the directors of the companies to enhance their manufacturing capabilities to keep them relevant to the manufacturing industries